A Brief Review and Its Incorporation with Bibliometric Analysis of Phase Change Materials for Thermal Energy Storage - Farikha Maharani; Indah Hartati (Research in Chemical Engineering, 2023)
Reduction of Food Losses and Wastes (FLW) through the use of cold chain is one strategy applied in accelerating the SDGs goals of zero hunger. The application of Thermal Energy Storage (TES) based on PCM (Phase Change Material) is considered as one of best efforts for the simultaneous reduction of food losses and wastes, reduction of energy consumption as well as preserve the right temperature for food product. This paper presents the review of phase change material for thermal energy purposes and its bibliometric analysis. Bibliometric analysis on term of cold chain logistics show that there is correlation between cold chain and terms of optimization, vehicle routing, carbon emission, refrigeration, and phase change materials. The definition of TES and PCM, as well as the advantages of TES based on latent material are described in this paper. PCMs is classified into solid-solid, solid-liquid, solid-gas and liquid-gas based on its phase. The potential generation of gas and larger volume on solid-gas and liquid-gas PCMs limits the application of those two types of PCMs. PCMs is also classified according to the phase change temperature in which low, medium and high temperature PCMs. Organic, inorganic and composite based PCMs are the classification of PCMs based on the chemical composition. Among the types of PCMs, this paper present a deep review of paraffin based organic PCMs. The appearance of term of thermal conductivity in bibliometric analysis on term of organic phase change materials is due to organic PCMs commonly have low thermal conductivity